2022
DOI: 10.3390/biomedicines10071647
|View full text |Cite
|
Sign up to set email alerts
|

A Fast, Reliable Oil-In-Water Microemulsion Procedure for Silica Coating of Ferromagnetic Zn Ferrite Nanoparticles Capable of Inducing Cancer Cell Death In Vitro

Abstract: The applications of ferrimagnetic nanoparticles (F-MNPs) in magnetic hyperthermia (MH) are restricted by their stabilization in microscale aggregates due to magnetostatic interactions significantly reducing their heating performances. Coating the F-MNPs in a silica layer is expected to significantly reduce the magnetostatic interactions, thereby increasing their heating ability. A new fast, facile, and eco-friendly oil-in-water microemulsion-based method was used for coating Zn0.4Fe2.6O4 F-MNPs in a silica lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 71 publications
(121 reference statements)
2
18
0
Order By: Relevance
“…It is also important to mention that recently, it was demonstrated that core-shell ferrite MNPs with a shell doped with Zn, exhibit an unusually high SAR [ 14 ]. As reported previously [ 34 ], these Zn ferrite MNPs exhibit very high SAR values, above 3 kW/g Fe , and are also nontoxic for both normal BJ and A459 cancer cell lines, up to a concentration of 0.8 mg/mL [ 35 ].…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…It is also important to mention that recently, it was demonstrated that core-shell ferrite MNPs with a shell doped with Zn, exhibit an unusually high SAR [ 14 ]. As reported previously [ 34 ], these Zn ferrite MNPs exhibit very high SAR values, above 3 kW/g Fe , and are also nontoxic for both normal BJ and A459 cancer cell lines, up to a concentration of 0.8 mg/mL [ 35 ].…”
Section: Introductionsupporting
confidence: 57%
“…The zinc ferrite NPs were synthesized following a thermal decomposition method of the acetylacetonate precursors [ 34 ]. The detailed synthesis method and the physicochemical characterization techniques as, transmission electron microscopy (TEM), X-ray diffraction (XRD), dynamic light scattering (DLS), Fourier transform infra-red spectroscopy (FTIR), and vibrating sample magnetometry (VSM) are presented in our previous paper [ 35 ]. Briefly, the as-synthesized MNPs have faceted shapes (some are cubic, others polyhedral) with the main size of 28 ± 0.2 nm and a good polydispersity index which was very close to the average crystalline size (27 nm), calculated using Scherrer’s formula by the Gaussian fit of the prominent X-ray diffraction peaks ( Figure S1 ) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations